A qualitative investigation of benchmarking barriers in Nigeria. Issue 7 (3rd October 2016) - Adewunmi, Yewande Adetoro; Koleoso, Hikmot; Omirin, Modupe
Abstract : Purpose: The purpose of this paper is to examine benchmarking barriers among Nigerian facilities management (FM) practitioners. Design/methodology/approach: Data collection were through semi-structured interviews with 34 FM heads from three selected cities in Nigeria. Out of this number, 16 were from Lagos, ten from Abuja while eight managers were from Port Harcourt, respectively. These managers were selected using purposive sampling based on their experience in the field of FM across the various sectors of the economy. The interviews were analysed with Nvivo 10 software qualitative computer software. Findings: Those that do informal benchmarking face challenges with data, employees lack of confidence in new initiatives and poor support of senior management, the companies that use best practice benchmarking face constraints of access to information and employees unwillingness to change and comply to company set standards, unwillingness of benchmarking partners to understand the usefulness of the project, and problems that emanate from the quality of data obtained. Practical implications: The results therefore suggest that to improve the practice of best practice benchmarking there is need to improve both quantity and quality of data for the exercise and enhance standard practice. Originality/value: The study established a new category of benchmarking barriers called the market category of benchmarking barriers and further distinguished benchmarking barriers based on two forms of benchmarking which is informal and formal benchmarking. Also there are limited studies on benchmarking barriers in developing countries.